2007
DOI: 10.1136/vr.160.10.336
|View full text |Cite
|
Sign up to set email alerts
|

PrP genotypes in a pedigree flock of Santa Inês sheep

Abstract: SCRAPIE is a prion disease of sheep and goats, and is characterised by the accumulation of pathologically folded prion protein (PrP) derived from host-encoded PrP. For sheep, over 40 polymorphisms of PrP have been described

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
3
10

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 15 publications
0
16
3
10
Order By: Relevance
“…Outros estudos envolvendo a raça Santa Inês, Lima et al (2007) mostraram que em 29 amostras genotipadas foram encontrados 9 alelos e 13 genótipos. Os resultados semelhantes demonstram que a raça Santa Inês possui grande variabilidade genética.…”
Section: Discussão E Conclusõesunclassified
See 2 more Smart Citations
“…Outros estudos envolvendo a raça Santa Inês, Lima et al (2007) mostraram que em 29 amostras genotipadas foram encontrados 9 alelos e 13 genótipos. Os resultados semelhantes demonstram que a raça Santa Inês possui grande variabilidade genética.…”
Section: Discussão E Conclusõesunclassified
“…Levando em consideração que essa combinação não é considerada resistente, ϐica claro que mais da metade do rebanho ovino analisado tem susceptibilidade ao desenvolvimento da doença. De maneira semelhante Sotomaior et al (2008) e Lima et al (2007) em seus estudos veriϐicaram a predominância do genótipo ARQ/ARQ nos animais analisados, sendo que nestas ocasiões foram analisadas amostras de animais criados no Brasil. Os resultados semelhantes demonstram que a raça nativa Santa Inês é potencialmente susceptivel ao scrapie.…”
Section: Discussão E Conclusõesunclassified
See 1 more Smart Citation
“…A survey conducted for this review of more than 20 studies [1,2,4,14,20,21,23,24,27,38,54,64,68,69,82,83,[86][87][88]90] reporting on sheep populations from 15 different countries in Europe, America and Asia revealed that so far all but one (Iceland) presented significant frequencies of all five major alleles (ARQ; ARR; AHQ; VRQ; ARH) in their sheep. Iceland appears not to have any ARR animals [86].…”
Section: Classical Scrapie In Sheepmentioning
confidence: 99%
“…Since then, some studies have analyzed variation in codons 136, 154 and 171 of the prion protein (Passos et al 2008, Lima et al 2007, Sotomaior et al 2008), but other codon variations in the PrP gene from Brazilian ovine and goat breeds have not been extensively analyzed.…”
Section: Introductionmentioning
confidence: 99%